PELATIHAN STRENGTH & CONDITIONING SE-WILAYAH III CIREBON, JAWA BARAT - Heru Mifakhudin; Okki Yonda (Prosiding Seminar Nasional Pengabdian Kepada Masyarakat, 2022)
AbstractPB Data. PELTI in March 2022 for the age category under 10-16 years, showed that there was only 1 player fromregion III Cirebon, a/n Fauzan Ahmad with a national rating of 4 in the 16 year old male age group, seeing thisdata it was considered that there was a deficiency in fostering and building regional athletes to be able to compete and have national rankings. Specific to the area of training and coach development in tennis, an area that must be improved Together is a matter of technical tactics and strength and conditioning, because this area is the foundation or wheel for carrying out how to implement athlete skills on the field. Techniques in tennis are not just being able to hit the ball just as much, but more like serve, return serve, rally, approaching and net game, and passing shot or lob, and even in terms of the most basic elements, namely balance, raquet face control and timing are indicators of tennis athletes that must be fulfilled perfect and must be able to do it effectively and efficiently, because these 5 things can deliver 50% help in creating a point. Tactics in tennis do not only talk about hitting consistency, but there are some things that must be mastered and stick to the 5 elements above, such as playing with an open court pattern, playing on weakness, playing variation, serve and volley, aggressive baseliner, counter puncher, behind the back, net rusher, 2 on 1, solid cross court, determining middle area, first taking initiative, high percentage. this tactic will help another 50% in creating points and of course victory. From the explanation above, not many coaches are aware that the supporting factor is strength and conditioning training so that players know which strength factors to strengthen, thus it is necessary to carry out community service activities with the title: Strength and Conditioning Training for Region III Cirebon, West Java. This activity is designed in order to make a fundamental contribution to regional trainers, physical education teachers as the target. Providing insight, knowledge and direct drill to physical education trainers and teachers about the theory and practice of Strength and Conditioning so as to provide provisions and opportunities in order to develop the activities of their students in the best and directed manner. The targeted output is in the form of the competence of trainers and teachers in fostering game sports in order to improve the quality of athlete human resources and trainer knowledge about how to train properly targeting region III Cirebon AbstrakData PB. PELTI pada bulan maret 2022 untuk kategori usia dibawah 10 – 16 tahun, menunjukkan hanya terdapat 1 orang pemain asal wilayah III Cirebon, a/n Fauzan ahmad dengan peringakat 4 nasional kelompok umur 16 Tahun putra, melihat data tersebut dinilai ada kekurangan dalam membina dan membangun atlet daerah untuk bisa berkompetisi dan memiliki peringkat nasional. Spesifik pada area kepelatihan dan pengembangan pelatih dalam olahraga tenis, area yang harus diperbaiki Bersama adalah persoalan taktik tehnik dan strength and conditioning, kerena area ini merupakan fondasi atau roda untuk menjalankan bagaimana implementasi kemampuan skill atlet dilapangan, Tehnik dalam tenis bukan hanya sekedar bisa memukul bola saja sebanyak banyaknya, tapi lebih seperti serve, return serve, rally, approaching and net game, dan passing shot or lob, dan bahkan untuk dari segi elemen paing dasar lagi yaitu balance, raquet face control dan timing merupakan indicator atlet tenis yang harus terpenuhi secara sempurna dan harus bisa melakukannya dengan efektif dan efisien, karena 5 hal ini bisa mengantarkan membantu 50% dalam menciptakan sebuah poin. Taktik dalam tenis bukan hanya berbicara konsistensi pukulan, namun ada beberapa yang harus dikuasai dan menempel dengan unsur 5 hal diatas, seperti, bermain dengan pola open court, playing on weakness, playing variation, serve and volley, aggressive baseliner, counter puncher, behind the back, net rusher, 2 on 1, solid cross court, determining middle area, first taking inisiative, high percentage. taktik ini akan membantu 50% lagi dalam menciptakan poin dan tentunya kemenangan. Penjelasan diatas tidak banyak pelatih yang sadar bahwa faktor pendukungya adalah latihan strength and conditioning sehingga pemain mengetahui faktor kekuatan mana yang harus kuatkan, dengan demikian perlu dilakukan kegiatan pengabdian masyarakat dengan judul: Pelatihan Strength and Conditioning Se-wilayah III Cirebon, Jawa Barat. Kegiatan ini dirancang dalam rangka memberikan kontribusi mendasar pada pelatih daerah, guru pendidikan jasmani sebagai sasaran. Pemberian wawasan, pengetahuan dan drill langsung terhadap pelatih dan guru-guru pendidikan jasmani tentang teori dan praktek Strength and Conditioning sehingga memberikan bekal dan peluang dalam rangka mengembangkan aktifitas muridnya dengan sebaik baiknya dan terarah. Luaran yang ditargetkan berupa kompetensi pelatih dan guru